Parents and Children During the COVID-19 Lockdown: The Influence of Parenting Distress and Parenting Self-Efficacy on Children’s Emotional Well-Being - Morelli, Mara; Cattelino, Elena; Baiocco, Roberto; Trumello, Carmen; Babore, Alessandra; Candelori, Carla; Chirumbolo, Antonio (Frontiers in Psychology, 2020)
On March 10, 2020 Italy went into lockdown due to the Coronavirus Disease-19 (COVID-19) pandemic. The World Health Organization highlighted how the lockdown had negative consequences on psychological well-being, especially for children. The present study aimed to investigate parental correlates of children's emotion regulation during the COVID-19 lockdown. Within the Social Cognitive Theory framework, a path model in which parenting self-efficacy and parental regulatory emotional self-efficacy mediated the relationship between parents’ psychological distress and both children’s emotional regulation, and children’s lability/negativity, was investigated. A total of 277 parents of children aged from 6 to 13 years old completed an online survey that assessed their psychological distress, regulatory emotional self-efficacy, and parenting self-efficacy. Parents reported also children’s emotional regulation and lability/negativity. A structural equation model using MPLUS 8.3 was tested. Results showed that the hypothesized model exhibited excellent fit, chi-square (83) = 140.40, p < .01, RMSEA = .05, CFI = .97, TLI = .96, SRMR = .04. The influences of parents’ psychological distress and parents’ regulatory emotional self-efficacy on children’s emotional regulation and lability/negativity were mediated by parenting self-efficacy. The mediation model was invariant across children’s biological sex and age, and geographical residence area (high risk vs. low risk for COVID-19). Results suggested how parents’ beliefs to be competent in managing parental tasks might be a protective factor for their children’s emotional well-being. Implications for intervention programs are discussed.